Year's best science fiction twelfth annual collection - Dozois, Gardner R. (New York, N.Y. St. Martin's Press, 1995)
A consistently award-winning collection once again provides the best science fiction stories of the year, featuring work by veterans and newcomers including Michael Bishop, Nancy Kress, Ursula Le Guin, Mike Resnick, Geoff Ryman, Brian Stableford, and many others.
Forgiveness day -- Ursula K. Le Guin -- The remoras / Robert Reed -- Nekropolis / Maureen F. McHugh -- Margin of error / Nancy Kress -- Cilia-of-gold / Stephen Baxter -- Going after old man Alabama / William Sanders -- Melodies of the heart / Michael F. Flynn -- The hole in the hole / Terry Bisson -- Paris in June / Pat Cadigan -- Flowering mandrake / George Turner -- None so blind / Joe Haldeman -- Cocoon / Greg Egan -- Seven views of Olduvai Gorge / Mike Resnick -- Dead space for the unexpected / Geoff Ryman -- Cri de coeur / Michael Bishop -- The sawing boys / Howard Waldrop -- The matter of Seggri / Ursula K. Le Guin -- Ylem / Eliot Fintushel -- Asylum / Katharine Kerr -- Red Elvis / Walter Jon Williams -- California dreamer / Mary Rosenblum -- Split light / Lisa Goldstein -- Les fleurs du mal / Brian Stableford
68904
Keywords: Science fiction, American; Short Stories